Analysis of factors influencing the adoption of MyTens application with the unified theory of acceptance and use of technology 2 (UTAUT 2) model on account managers at Telkom Indonesia - Wiryawan, Yosef Febri; Tricahyono, Dodie; Awaluddin, Muhammad (Goodwood Publishing, 2024)
Purpose: To support the Five Bold Moves strategy, Telkom Indonesia launched the MyTEnS application to streamline B2B processes for Account Managers (AM). This study investigates the factors influencing MyTEnS adoption and the moderating roles of Age and Job Tenure. Research methodology: A quantitative method was employed using the extended UTAUT-2 model, incorporating Personal Innovativeness and moderation by Age and Job Tenure. A total of 129 respondents participated, and data were analyzed using SmartPLS 3.0 with path analysis. Results: Effort Expectancy, Hedonic Motivation, and Personal Innovativeness significantly influence Behavioral Intention. Facilitating Conditions and Behavioral Intention significantly affect Use Behavior. Meanwhile, Performance Expectancy, Social Influence, and Habit show no significant effect on Behavioral Intention. Moderating effects of Age and Job Tenure were significant only in the relationship between Facilitating Conditions and Behavioral Intention. Conclusions: Personal Innovativeness emerged as the strongest predictor of Behavioral Intention, followed by Hedonic Motivation and Effort Expectancy. Behavioral Intention is the most significant factor influencing actual system usage. Limitations: The study is limited by its cross-sectional design and focus on a single organization. Some hypotheses were unsupported, possibly due to limited construct measurement. Contribution: This study extends the UTAUT-2 model with new variables and offers insights into B2B technology adoption within a telecommunications context.